PERLINDUNGAN HUKUM TERHADAP PESERO FIRMA KETIKA SALAH SEORANG PESERO MELAKUKAN TIDAKAN HUKUM YANG MENIMBULKAN KERUGIAN PADA PERSEROAN - Nugraha, Fx. Sri (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2024)
Firms that are synonymous with partnerships (maatschap) are cooperation between people who are friends or friends or fellowships, can be friends in the same profession or friends in trade. The firm is not a legal entity, the most important basis for the establishment of a firm is trust, therefore responsibility within the firm is joint responsibility because whatever happens within the firm is shared, including things that cause losses. Based on these problems, this research method is normative or doctrinal, the object of which is statutory regulations with a case and doctrine approach, then the primary legal materials are statutory regulations and secondary legal materials are books and journals. The results of this study are first that this responsibility has been emphasized in the Civil Code Article 1628-1633 that the responsibility of the shareholder for losses that occur is that if it concerns personal receivables involving the company then the payment that occurs is all of the shareholder's receivables to third parties, and the company's affairs must take precedence over personal matters and the provisions in the agreement that when a loss is incurred personally by the company, it becomes the responsibility of the company, if not, the responsibility is equal to the input in the company. Meanwhile, the responsibility in the company by the partner is joint responsibility including external and internal responsibility.